Challenging colonial authority principalia vs, priest in 19th century Kabikolan - Owen, Norman G. (2001)
The principalía- municipal officials and ex-officials- were the recognized leaders of Filipino society under Spanish rule, yet they are frequently portrayed as powerless victims or tools of Spanish friars. Examination of archival records on Kabikolan in the early 19th-century suggests, however, that within the framework of colonial rule they were more free to maneuver, and even to resist, than is generally recognized. In between day-to-day compliance (or non-compliance) and outright rebellion or withdrawal from the colonial system, there were occasional opportunities for the Bicolano principales to argue back, and sometimes even to win reversal of policies that threatened their municipal or class interests. In this paper we look at what happened in Cagsaua after the eruption of 1814, when the townspeople refused to move to Putiao (Pilar) and insisted on resettling in Daraga instead. By examining this and other cases of local principales resisting colonial authority, we can discern some of the common elements in such successful challenges. These included both maintenance of the appearance of unity within the local community and some skill in manipulating Spanish language and law. If we see the principalía as active agents- not just passive pawns- within the framework of colonial politics, we are better able to understand how they were able to dominate the ordinary timawas and to survive as a class, becoming the 20th-century Bicolano elite.
Includes bibliographical references (pages 123-127).